Coordinated optimisation of PEV charging with the support of reactive discharging and phase switching in unbalanced active distribution networks. Issue 21 (22nd September 2020) - Fu, Yang; Meng, Xianghao; Su, Xiangjing; Jabalameli, Nasim; Dong, Zhaoyang
Abstract : Plug‐in electric vehicles (PEVs) are being widely deployed, especially in the residential premises. Random PEV charging causes negative impacts on the power grid, a coordinated PEV charging is essential. Currently, PEV charging studies mainly focus on the active power control of PEVs while there is a risk of worse operation, due to the transferring of charging load instead of eliminating. Besides, existing PEV charging studies are commonly based on a three‐phase balanced network model, but practical distribution networks, especially on the low‐voltage level, are unbalanced. This study proposes a novel coordination strategy of PEV charging in unbalanced distribution networks, with the support of reactive discharging and phase switching. The optimisation model of PEV charging is firstly proposed to minimise the network loss and charging cost while maximising users' benefit from ancillary reactive service. The optimal power flow problem defined above is solved by a combined solver of discrete particle swarm optimisation and direct load flow. Then, a coordination strategy of PEV charging, reactive discharging and phase switching is presented to apply the proposed optimisation over 24 h. Finally, detailed simulations are conducted on a real Australian distribution network, to test the feasibility and effectiveness of the proposed optimisation and coordination strategy of PEV charging in unbalanced distribution networks.